Blood product administration during high risk neuroblastoma therapy. (2nd January 2020) - Silverstein, Allison; Reddy, Kiranmye; Smith, Valeria; Foster, Jennifer H.; Russell, Heidi V.; Whittle, Sarah B.
Abstract: The increasing intensity of high-risk neuroblastoma (HR NB) treatment over the last decades has resulted in improved survival at the expense of prolonging therapy and exposure to additional potentially toxic agents. Anemia and thrombocytopenia requiring transfusion are common during therapy for HR NB. Risks of cumulative red blood cell and platelet transfusions are incompletely defined in pediatric oncology patients, however, risks of transfusional iron overload are well described in other populations. This study aimed to determine the number of packed red blood cell (pRBC) and platelet transfusions throughout treatment for HR NB and how these numbers have changed with modern therapy. We performed a retrospective review of 92 patients with HR NB from June 2002 until September 2017. Patients received a median of 20 pRBC and 32 platelet transfusions. Our results demonstrated large numbers of transfusions with significantly increased blood product exposures among patients who received intensified therapy, either with additional induction chemotherapy, tandem autologous stem cell transplants, or dinutuximab plus cytokines with isotretinoin. Similar volumes of pRBC transfusions have been associated with iron overload in other populations and warrant further discussion of guidelines for long-term follow up of HR NB patients.